Development and catalytic mechanism of a highly efficient Pt/Kβ catalyst for n-Heptane aromatization. (1st April 2023) - Zhou, Qiuming; Chen, Yanyan; Fan, Sheng; Wang, Sen; Qin, Zhangfeng; Dong, Mei; Wang, Jianguo; Fan, Weibin
Graphical abstract: Highlights: A high-performance catalyst has been developed for naphtha aromatization. Pt NPs and Brϕnsted acid sites synergetically catalyze the reaction. K + weakens Brϕnsted acidity, transfers electrons to Pt and creates mesopores. The reaction occurs via dehydrogenation (DH), cyclization, ring-expansion and/or DH. Abstract: Development of a high-performance naphtha aromatization catalyst has been paid many attentions as this reaction is generally employed to elevate the octane number of FCC gasoline and Fischer-Tropsch-synthesized oil. Here, a hierarchical porous Pt/Kβ catalyst is developed. It shows much higher activity, selectivity and stability than conventional Pt/KL. The catalytic performance of Pt/Kβ depends on Brϕnsted acidity and mesoporosity of zeolite β and nanoparticles (NPs) size and electronic state of Pt. The catalytic mechanism was investigated by combining TPSR, GC–MS, reaction kinetic studies and DFT calculations. Pt NPs catalyze dehydrogenations of alkanes/cycloalkenes to alkenes and dienes, while Brϕnsted acid sites facilitate alkene cyclization and ring-expansion of cycloalkenes despite that they can also dehydrogenate alkanes/alkenes through hydrogen transfer reactions. The n -heptane is mainly aromatized by dehydrogenating to 1-heptene and 2-heptene, 1, 6- and 1, 5-cyclizing into methylcyclohexane and ethyl-cyclopentane, and successively ring-expanding and/or dehydrogenating to toluene that may be further dealkylated to benzene.